August Strindberg: The Occult Diary Paris 1896 - Stockholm 1908 - Stam, Per; Gavel Adams, Ann-Charlotte; Engwall, Gunnel (Critical Editions in Culture and Aesthetics, 2022)
August Strindberg (1849-1912) kept a diary from February 1896 in Paris until the summer of 1908 in Stockholm. He referred to his diary from this period as his Occult Diary and used it to help him decipher the world as he experienced it. He read and reread his own notations, adding new interpretations, and deleting others. He also drew on the diary as material for creative expression, transforming isolated events and observations into groundbreaking works of literature. The Occult Diary is published here in its entirety in English translation for the first time, in a final revision by Ann-Charlotte Gavel Adams and with an introduction by Per Stam. The Occult Diary is a key resource for international Strindberg scholars and theater professionals and more broadly for scholars focusing on drama, theater history, stage performance, and literary currents at the turn of the previous century. The diary initiates the reader into the writer's inner world during a crucial transitional period in his personal and literary life. It documents his readings and observations and gives important clues and information about an ongoing process of artistic reorientation. Strindberg was exploring new ways of looking at, interpreting, and writing about nature, science, art, the occult, and his fellow human beings.